PROMOTIONAL BLOGS FOR [NEW] BOLD MUKU PROJECT - Henny S. Tansy; Theophilus J. Riyanto (Institute of Research and Community Outreach - Petra Christian University, 2015)
Promotional blogs for [NEW] Bold MUKU Project were inspired by the current situation when Indonesian teenagers have no big interest in reading books because of the digital media. In 2011, a book-sharing movement, Bold MUKU Project, tried to track back Indonesian teenagers’ reading interest and yet did not work successfully due to the unspecific target market, the lack of planning, sources, and member structuring. Therefore, the promotional blogs must be created based on the interest of the target audience and relevant concepts. The results of the surveys and the concepts of Internet consumer behavior and theory of copywriting by Rob Bowdery are considered to create promotional blogs for [NEW] Bold MUKU Project, that is, the main blog and an Instagram account. The main blog provides information and discussion among the community. The second promotional blog is Instagram as a place to attract viewers to open the main blog. In conclusion, in order to have successful promotional blogs, the contents of the promotional blogs must fit to the target audience’s interests and needs.